ANALISIS FAKTOR YANG DAPAT MEMPENGARUHI INCOME SMOOTHING PADA PERUSAHAAN MANUFAKTUR DI BEI - Yusuf Efendi, Lukman Surjadi (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this study is to empirically examine the influence of firm size, return on asset, net profit margins, and financial leverage towards income smoothing practice in manufacturing companies listed in Indonesia Stock Exchange from period 2016 – 2018. This study used 62 data from manufacturing companies that have been selected using purposive sampling method with total 186 data for three years. The data used are secondary data in the form of financial statements. This research used econometric views (E-Views) version 10 software to process the data. The result of research shows that return on asset has negative significant and net profit margnis has positive significant influence towards income smoothing practice, firm size and net profit margins have no significant influence towards income smoothing practice.